2021
DOI: 10.3390/met11030484
|View full text |Cite
|
Sign up to set email alerts
|

Determining Forming Limit Diagrams Using Sub-Sized Specimen Geometry and Comparing FLD Evaluation Methods

Abstract: Sheet metal forming boundaries are established using the forming limit diagram (FLD). The Nakajima and Marciniak tests, which are based on stretching a material using a punch, are the most commonly used methods for determining the FLD or fracture forming limit diagram (FFLD). The results are usually evaluated by calculating local strain, strain rates, specimen thickness reduction or fracture strain. When the amount of experimental material is insufficient, miniaturization of the testing specimens may be a solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Good lubrication results in flow localization occurring near the pole, whereas in the case of poor lubrication, flow localization occurs near the flange. Rubesˇova´et al 4 targeted the results obtained from sub-size specimens and compared the FLC of these specimens with that of standard specimens. They found that good accordance was achieved between the FLC of sub-sized and standard specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Good lubrication results in flow localization occurring near the pole, whereas in the case of poor lubrication, flow localization occurs near the flange. Rubesˇova´et al 4 targeted the results obtained from sub-size specimens and compared the FLC of these specimens with that of standard specimens. They found that good accordance was achieved between the FLC of sub-sized and standard specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In all forming operations using sheet metal as an input material, it is critical to understand the conditions that cause necking (instability of material) or fracture. Such limits can be represented as a forming limit diagram (FLD) shown in Figure 2, which plots the curve of major and minor strain coordinates [11]. The strain in the direction of the maximum strain is defined as the major strain.…”
Section: Introductionmentioning
confidence: 99%